Dry reforming of methane in gliding arc plasma: bridging thermal and post-plasma catalysis - O’Modhrain, Colin; Pajares, Arturo; Coutino-Gonzalez, Eduardo; de Vos, Yoran; Guardia, Pablo; Gorbanev, Yury; Michielsen, Bart; Bogaerts, Annemie (EES catalysis, 2025)
This study compares thermal and post-plasma catalysis for dry reforming of methane (DRM) using nickel–alumina catalyst spheres. The optimum catalyst loading was first determined by thermo-catalytic performance testing and characterization. The selected catalyst spheres (4 wt% Ni loading) were introduced to a novel post-plasma-catalytic bed, designed to utilize the sensible heat from the plasma reactor and boost the DRM reaction without additional heating. A parametric scan of inlet CH 4 fractions (10–50 vol%) consistently shows improved CH 4 conversion in the presence of a catalyst. The CO and H 2 production rates reach peak values of ca. 24.4 mol mol Ni −1 min −1 with 40 vol% CH 4 at the inlet, at a minimum energy cost (EC) of around 0.24 MJ per mol of reactant mixture. Interestingly, the addition of catalyst does not benefit the EC, but instead results in an improved syngas (H 2 /CO) ratio for 10–30 vol% CH 4 . In addition, a long-run post-plasma-catalytic test (6 h) demonstrates stable conversion and syngas ratio values. The EC obtained in this study is by far the lowest reported in post-plasma-catalytic DRM to date, and the insulated bed design reduces the heat loss from the bed and enables a more stable output. The successful coupling of a thermo-catalytic catalyst selection process with implementation in a post-plasma-catalytic bed demonstrates the coupling potential that can be realized between both research domains.